О сильно модифицированной новой копеподе Colpocyclops dulcis gen. et sp. n. (Crustacea, Cyclopidae) - Монченко, В.И. (Вестник зоологии, 1977)
The females and males of Colpocyclops dulcis M o n c h e n k o, gen. et sp. n. from the Lower Dnieper are described and figured. The new genus occupies a fully isolated position among other genera of Cyclopidae because of a complete absence of maxillipeds and an unusial modification of other mouth legs: a strongly developed apical part of the maxillular palp and reduced number of lateral setae, a hypertrophy of one of the spines on the second maxillar joint on which the last (third) joint forms only a minor lateral appendage, and other signs of modification.